2015
DOI: 10.1089/ten.tea.2014.0115
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Performance of Donor-Matched Human Adipose and Bone Marrow Mesenchymal Cells Under Dynamic Culture

Abstract: Adipose-derived mesenchymal cells (ACs) and bone marrow-derived mesenchymal cells (BMCs) have been widely used for bone regeneration and can be seeded on a variety of rigid scaffolds. However, to date, a direct comparison of mesenchymal cells (MC) harvested from different tissues from the same donor and cultured in identical osteogenic conditions has not been investigated. Indeed, it is unclear whether marrow-derived or fatderived MC possess intrinsic differences in bone-forming capabilities, since within-pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 28 publications
3
36
0
3
Order By: Relevance
“…Comparative studies with ADSCs and bone marrow-derived MSC described minor differences regarding their differentiation potential and their immunomodulatory activity [16,17]. Thus, bone marrow-derived MSCs had a slightly better osteogenic capacity, but ADSCs show a more effective collagen production.…”
Section: Isolation and Characterizationmentioning
confidence: 99%
“…Comparative studies with ADSCs and bone marrow-derived MSC described minor differences regarding their differentiation potential and their immunomodulatory activity [16,17]. Thus, bone marrow-derived MSCs had a slightly better osteogenic capacity, but ADSCs show a more effective collagen production.…”
Section: Isolation and Characterizationmentioning
confidence: 99%
“…14,15 An intraindividual comparison of human MSCs of three donors cultured on decellularized porcine bone confirmed superior osteogenic capacity of BMSCs compared to ASCs. 16 On the other hand, a study by Rath et al found better osteogenic differentiation of ASCS compared to BMSCs using 3D bioglass scaffolds as a particular culturing condition. 17 Brennan et al isolated human BMSC from bone marrow aspirates and ASCs from lipoaspirates of healthy donors and characterized the cells based on surface markers and tri-lineage differentiation as outlined above.…”
Section: Introductionmentioning
confidence: 97%
“…Another positive aspect of ADSCs is that they are genetically and morphologically stable. Research data suggest that MSCs have a slight advantage where osteogenic capacity concerned [39]. On the other hand, ADSCs seem to be more efficient for collagen production [40].…”
Section: Possible Application and Challenges Of Epithelial Cells In Hmentioning
confidence: 99%